Chicken ovalbumin upstream promoter transcription factor binds to a negative regulatory region in the human immunodeficiency virus type 1 long terminal repeat. - Cooney, A J (1991)
The human immunodeficiency virus type 1 (HIV-1) long terminal repeat (LTR) contains a negative regulatory element (NRE) which downregulates the rate of LTR-directed transcription and HIV-1 replication. Within the NRE is a GGTCA palindrome, which binds a possible member of the steroid/thyroid hormone receptor superfamily. Mutation of this site leads to an increase in LTR-directed transcriptional activity compared with the wild type, consistent with the element's being a functional part of the NRE. The palindrome contains significant identity to the chicken ovalbumin upstream promoter (COUP) element to which COUP transcription factors (COUP-TFs), members of the steroid/thyroid hormone receptor superfamily, bind. We demonstrate here that human COUP-TFs can bind specifically to this HIV-1 COUP-like element in a manner identical to binding to ovalbumin COUP. We show that the predominant COUP-TF family member synthesized in T cells is the 68-kDa form, which is likely to be responsible for any in vivo function of the HIV-1 COUP-like element in these cells. Finally, we have identified three HIV-1 variant strains that contain mutations in the HIV-1 COUP-like element which affect the binding affinity of COUP-TF for these variant COUP elements.